Appraisal Systems and Employees’ Performance in Local Governments in Uganda: A Case Study of Kabale District Local Government. - Muruhura, Abel (Kabale University, 2024)
The study examined Appraisal Systems and Employees’ Performance in Local Governments in Uganda: A Case Study of Kabale District Local Government, aimed to analyze the effect of performance planning, determine the relationship between performance monitoring and assess the impact of performance improvement on employee performance. A cross-sectional research design was used, with a sample size of 160 selected from a population of 266 using Slovin's formula. Stratified random sampling was applied to select respondents from various roles, including teachers, administrators, and district staff. Data collection methods included questionnaires, interviews, and documentary reviews. The findings revealed a strong positive correlation between performance planning and employee performance (r = 0.626, p < 0.000), indicating that setting specific, measurable goals aligned with organizational objectives enhances performance. Similarly, performance monitoring showed a strong correlation with employee performance (r = 0.621, p < 0.000), though inconsistencies were noted in appraising core competencies. Performance improvement also had a significant positive impact on performance (r = 0.629, p < 0.000), though feedback processes were found to be inconsistently applied. The study concluded that effective appraisal systems significantly improve employee performance but highlighted areas for improvement in appraisals and feedback. Recommendations included integrating Key Performance Indicators (KPIs), enhancing feedback mechanisms, and promoting two-way communication to ensure a more comprehensive and consistent appraisal process.